Interactive Association Between Intronic Polymorphism (rs10506151) of the LRRK2 Gene and Type 2 Diabetes on Neurodegenerative Diseases - Huang MH; Liu YF; Nfor ON; Hsu SY; Lin WY; Chang YS; Liaw YP (Dove Medical Press, 2021)
Mei-Hsuen Huang,1 Yu-Fan Liu,2,3 Oswald Ndi Nfor,4 Shu-Yi Hsu,4 Wei-Yong Lin,5- 7 Yuan-Shiun Chang,1 Yung-Po Liaw4,8 1Department of Chinese Pharmaceutical Sciences and Chinese Medicine Resources, College of Chinese Medicine, China Medical University, Taichung, 40402, Taiwan; 2Department of Biomedical Sciences, Chung Shan Medical University, Taichung, Taiwan; 3Division of Allergy, Department of Pediatrics, Chung Shan Medical University Hospital, Taichung, Taiwan; 4Department of Public Health and Institute of Public Health, Chung Shan Medical University, Taichung, 40201, Taiwan; 5Graduate Institute of Integrated Medicine, College of Chinese Medicine, China Medical University, Taichung, 40402, Taiwan; 6Department of Medical Research, China Medical University Hospital, Taichung, 40447, Taiwan; 7Brain Diseases Research Center, China Medical University, Taichung, 40402, Taiwan; 8Department of Medical Imaging, Chung Shan Medical University Hospital, Taichung City, 40201, TaiwanCorrespondence: Yung-Po LiawDepartment of Public Health and Institute of Public Health, Chung Shan Medical University, No. 110, Sec. 1 Jianguo N. Road, Taichung City, 40201, TaiwanTel +886-4-24730022 ext.11838Fax +886-4-23248179Email Liawyp@csmu.edu.twYuan-Shiun ChangDepartment of Chinese Pharmaceutical Sciences and Chinese Medicine Resources, College of Chinese Medicine, China Medical University, Taichung, 40402, TaiwanTel +886-4-22053366 ext. 5502Fax +886-4-22083362Email yschang@mail.cmu.edu.twPurpose: We investigated the interactive effect of rs10506151 polymorphism of the Leucine-rich repeat kinase 2 (LRRK2) gene and type 2 diabetes (T2D) on neurodegenerative disease (ND) risk.Materials and Methods: Data of 17, 927 participants in the Taiwan Biobank (TWB) assessed between 2008 and 2015 were linked to healthcare records in the National Health Insurance Research Database (NHIRD). The odd ratios (ORs) and 95% confidence intervals (CIs) for NDs were determined using logistic regression analysis.Results: There were 145 cases with NDs, and 28.28% (n = 41) of these individuals had T2D. Associations of neurodegenerative disorders with LRRK2 rs10506151 variant and T2D were not significant. The corresponding ORs (95% CI) for NDs were 1.06 (0.75- 1.49) in CA/AA compared to CC individuals and 0.93 (0.63- 1.39) in those with T2D compared to non-diabetic participants. However, we found evidence of a significant interaction between rs10506151 and T2D (p = 0.0073). After stratification by genotypes of rs10506151, the OR for NDs was 0.37 (CI, 0.17- 0.82) in CA/AA individuals with T2D and 1.41 (0.88- 2.27) in their CC counterparts. When CA/AA individuals with T2D represented the reference group, the OR (95% CI) was 1.74 (0.81- 3.73) in CC individuals with no T2D, 2.47 (CI, 1.14- 5.38) in CA/AA individuals with no T2D, and 2.34 (CI, 1.07- 5.11) in CC individuals with T2D.Conclusion: Our data indicated that the risk of NDs was significantly lower among diabetic individuals with combined CA/AA of the LRRK2 rs10506151 variant in Taiwan.Keywords: polymorphism, neurodegenerative disorders, diabetes, variation